2023
DOI: 10.1021/acsaem.2c03655
|View full text |Cite
|
Sign up to set email alerts
|

High-Entropy Alloys FeCoNiCuX (X = Al, Mo)-Ce0.8Sm0.2O2 as High-Performance Solid Oxide Fuel Cell Anodes

Abstract: High-entropy alloys (HEAs) have received a lot of attention in electrocatalysis due to their potent synergistic effects of uniformly mixing many elements. In this study, HEAs FeCoNiCuX (X = Al, Mo)-Ce0.8Sm0.2O2 (SDC) are considered as a prospective intermediate temperature solid oxide fuel cell (SOFC) anode. FeCoNiCuX-SDC as a SOFC anode shows comparable high conductivity with a Ni-based anode and exhibits outstanding catalytic capability for H2, CH4, and CO2. The LSGM electrolyte-supported single cell with Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…X-ray diffraction (XRD) analysis indicated that the as-synthesized FCNCM exhibited a single-phase metal structure, with no detectable presence of other oxides (Figures 1b and S1). The diffraction peaks at approximately 44 and 51°c orresponded to the (111) and (200) crystal planes of the facecentered cubic (FCC) structure, 31 with lattice distances of 2.2 and 1.9 Å, respectively. When compared to diffraction patterns of pure metals and binary alloy (Figures 1b and S2), it was evident that the diffraction peaks of FCNCM closely resembled those of Co 0.5 Ni 0.5 (PDF#04−004−8490), with noticeable shifts relative to the simple metal phases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray diffraction (XRD) analysis indicated that the as-synthesized FCNCM exhibited a single-phase metal structure, with no detectable presence of other oxides (Figures 1b and S1). The diffraction peaks at approximately 44 and 51°c orresponded to the (111) and (200) crystal planes of the facecentered cubic (FCC) structure, 31 with lattice distances of 2.2 and 1.9 Å, respectively. When compared to diffraction patterns of pure metals and binary alloy (Figures 1b and S2), it was evident that the diffraction peaks of FCNCM closely resembled those of Co 0.5 Ni 0.5 (PDF#04−004−8490), with noticeable shifts relative to the simple metal phases.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, control of lattice distortion in high-entropy alloys offers a unique approach for enhancing their oxidation-resistant capability . Extensive research has confirmed that properly designed high-entropy alloys can achieve high electrocatalytic and thermocatalytic activity such as oxygen evolution reaction, ammonia decomposition, and CO 2 hydrogenation. Some thoughtfully designed HEAs show excellent resistance to carbon deposition in solid oxide fuel cells (SOFCs), , but the performance and mechanism of HEAs in SOECs have not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the LF‐R p is dramatically reduced, indicative of the significantly enhanced CH 4 absorption/dissociation kinetics after Ru dual‐exsolution. [ 33 ]…”
Section: Resultsmentioning
confidence: 99%
“… I−V and I−P curves of the CH 4 fueled single cells using a) SFM/GDC anode and b) Ru@Ru‐SFM/Ru‐GDC anode, c) EIS curves and d) DRT analysis, e) cell potential as function of elapsed time for the Ru@Ru‐SFM/Ru‐GDC single cell, f) comparison of the peak power densities of CH 4 fueled single cells (Sr 2 Fe 1.5 Mo 0.5 O 6–δ (SFM), [ 9a ] Sr 2 ZnMoO (R‐SZMO), [ 25 ] Co@Sr 2 Fe 1.3 Co 0.2 Mo 0.5 O 6‐δ (Co@SFCM), [ 26 ] CoNiMo/Sr 2 FeMoO 6–δ (CNM/SFM), [ 27 ] CoFe@La 0.5 Ba 0.5 Mn 0.8 Fe 0.1 Co 0.1 O 3‐δ (CoFe@LBMFC), [ 28 ] Pr 6 O 11 ‐PrBaMn 2 O 5+δ (Pr‐PBMO), [ 29 ] Ni@La 0.4 Sr 0.4 Ti 0.85 Ru 0.07 Ni 0.08 O 3−δ (Ni@L0.4STRN), [ 30 ] Ni@(La 0.2 Sr 0.8 ) 0.925 Ti 0.55 Mn 0.35 Ni 0.1 O 3‐δ (Ni@LSTMN), [ 31 ] NiFe@La 0.6 Ce 0.1 Sr 0.3 Fe 0.9 Ni 0.1 O 3‐δ (NiFe@CLSFNi), [ 32 ] FeCoNiCuAl‐Sm 0.2 Ce 0.8 O 2 (FeCoNiCuAl‐SDC) [ 33 ] ). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation